(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Non-adherence to good manufacturing practice alongside improper handling during dispensing, packaging and inadequate post-marketing surveillance of pharmaceutical products accounts to product’s deterioration reduced therapeutic effect and adversely affects patient’s safety especially the paediatrics. This study evaluates the microbiological quality of various brands of paediatric cough syrups marketed and used within Port Harcourt metropolis. Twenty cough syrup brands were experimented on in duplicate, coded as USS and UNS (used and unused respectively). They were subjected to organoleptic assessment, pH, viscosity, total aerobic viable count, as well as resistance- susceptibility test of isolates using standard conventional techniques. Results showed viscosity value of 0.22 - 9.09 Pascal seconds (Pa.s), pH values of 3.13 - 8.34 across the UNS and USS categories respectively. While 80% of the UNS cough syrup samples were free from potential microbial threat, 20% fraction and all USS cough syrup (100%) samples were contaminated with objectionable microorganisms and non-compliant with USP permissible limit. The potentially pathogenic isolates were Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia, demonstrating varied resistance pattern to exposed antibiotic categories. Microbial contamination might have been caused by poor quality control and improper handling of the products during use. This calls for more stringent measures during product manufacturing and handling to ensure patient’s safety and forestall possible transference of resistance strain.